The Effect of Concentration and Immersion Time of Sodium Hydrogen Sulfites as an Anti-Browning Agent in Sliced Apples (Malus sylvestris Mill.) - Utama, Nafi; Nusivera, C.D.; Prabasari, Indira; Setiawan, Chandra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Sodium hydrogen sulfite or sodium bisulfite (NaHSO3) is a common anti-browning agent to preserve fresh produce. We can maintain the color of fruits and vegetables by inhibiting certain enzymes involved in the browning process. The study evaluates different concentrations (50, 100, 150, and 200 ppm) and immersion time (three and five minutes) of NaHSO3 applied to fresh-cut apples. Sliced apples (n=189 slices) were grouped into nine groups: N50I3 (50 ppm NaHSO3 immersion for three minutes), N100I3 (100 ppm NaHSO3 immersion for three minutes), N150I3 (150 ppm NaHSO3 immersion for three minutes), N200I3 (200 ppm NaHSO3 immersion for three minutes), N50I5 (50 ppm NaHSO3 immersion for five minutes), N100I5 (100 ppm NaHSO3 immersion for five minutes), N150I5 (150 ppm NaHSO3 immersion for five minutes), N200I5 (200 ppm NaHSO3 immersion for five minutes) and control group. The samples were compared between groups for peroxidase activity (unit/min), polyphenol oxidase activity (unit/min), phenolic content (ppm), total antioxidant activity (%), and discoloration (hue) every three days for 15 days. The results showed that immersing freshly cut fruit of Manalagi apples in NaHSO3 50 ppm for three minutes was the best treatment for inhibiting the enzymatic browning process compared to other treatments. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 5: Industry, Innovation and Infrastructure